2015
DOI: 10.1002/14651858.cd004081.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine for preventing postoperative sore throat

Abstract: In our revised systematic review, although the results of included studies show generally positive results, they should be interpreted carefully. The effect size of lidocaine appeared to be affected by study quality; drug concentration; route of administration; management of cuff pressure during anaesthesia; the included population; and the type of outcome measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 52 publications
4
63
0
7
Order By: Relevance
“…Lignocaine topicalization is commonly used to provide airway anesthesia to facilitate open airway procedures. Other uses include: tracheal intubation in the absence of neuromuscular blockade , reduction of the incidence of coughing and laryngospasm on induction or emergence from general anesthesia , attenuation of the haemodynamic changes to laryngoscopy , attenuation of bronchial hyper‐reactivity , and reduction in the incidence of postoperative sore throat .…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocaine topicalization is commonly used to provide airway anesthesia to facilitate open airway procedures. Other uses include: tracheal intubation in the absence of neuromuscular blockade , reduction of the incidence of coughing and laryngospasm on induction or emergence from general anesthesia , attenuation of the haemodynamic changes to laryngoscopy , attenuation of bronchial hyper‐reactivity , and reduction in the incidence of postoperative sore throat .…”
Section: Indicationsmentioning
confidence: 99%
“…We could find no evidence of the impact of lignocaine on postoperative sore throat in children. A systematic review of the effect of lignocaine on postoperative sore throat in adults concluded that both topical and intravenous lignocaine reduced the incidence and severity of sore throat after anesthesia with a tracheal tube . Only five of the 15 studies reviewed showed a reduction in sore throat and three of the studies demonstrated an increase in sore throat.…”
Section: Indicationsmentioning
confidence: 99%
“…We compared ketamine with numerous comparators that have been proven to prevent postoperative sore throat, [15][16][17][18][19][20][21] including topical lidocaine and corticosteroids as well as intravenous dexamethasone. However, comparisons of these treatments were performed in a limited number of small-sized studies, and the non-superiority Ketamine administration is associated with unwanted outcomes such as psychomimetic effects and blood pressure rise.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic process has been suggested to involve direct mucosal injury and inflammation related to airway instrumentation and presence of foreign airway objects [5]. Excessive cuff pressures of airway devices have been implicated as a cause of POST [6,7].…”
Section: Introductionmentioning
confidence: 99%